Enacting Language Assessment Syllabi: Teacher Educators’ Perspectives on Bridging Policies, Standards, and Practice in EFL Teachers’ Classrooms at Farhangian University - Ahmadizadeh, Masoumeh; Khodabakhshzadeh, Hossein; Rostamian, Morteza; Ashraf, Hamid (Assessment and Practice in Educational Sciences, 2026)
This study extends previous research on curriculum alignment in assessment education. Drawing on semi-structured interviews with ten teacher educators at Farhangian University, it explores how language assessment syllabi are enacted in practice in EFL teacher courses. Following the approach suggested by DeLuca and Bellara (2013), who emphasized the need for qualitative inquiry into the enactment of assessment curricula, the study investigates how teacher educators interpret and apply language assessment course syllabi expectations in real classroom contexts, with a focus on the extent to which courses descriptions and learning objectives align with education policy documents and formal curriculum standards.  Using reflexive thematic analysis, five themes were identified: structural and practical constraints; the strengths and weaknesses of the current syllabi; partial alignment with curriculum standards but limited familiarity with policy directives; aspects of assessment most frequently emphasized in teaching ; and principles left abstract or neglected, including fairness, washback, and assessment for learning. These findings indicate that while the syllabus offers a solid theoretical foundation, the translation of this foundation into classroom practice is constrained by time pressures, rigidity of the syllabus, and varying levels of student preparedness. In addition, the use of outdated resources further reduced opportunities for hands-on learning. The findings point to the need for stronger assessment literacy that goes beyond procedures and includes fairness, AfL, and practices suited to local contexts. Pedagogical implications are discussed with respect to syllabus design, the professional development of teacher educators, and how policy goals can be applied in classroom settings.